The 1920s London-Irish theatre - O'Ceallaigh Ritschel, Nelson, author. aut Link Link
1 online resource.
Keywords: "The 1920s London-Irish Theatre: A History documents, explores and interrogates the Irish Theatre that was prevalent in London during the 1920s. This includes consideration of the movements that impacted 1920s London theatre, such as the influential repertory theatres of the first decade of the twentieth century, as well as the detailed history of the Irish Players. Each identified London-Irish production is discussed through contemporary theatre reviews from London newspapers and journals, and within the decade's historical context. Dramatists, their plays, actors, producers, and the physical theatres are all considered as extensively as evidence allows. Major productions, like those of Lennox Robinson's The White-Headed Boy, Sean O'Casey's Juno and the Paycock, and Shaw's Saint Joan with its distinct Irish echoes are considered, along with productions of George Shiels' Professor Tim and Bernard Duffy's The Counter Charm and more. Producers discussed include James Fagan and Charles Macdona, while considered actors include Sara Allgood, Maire O'Neill, Arthur Sinclair, Fred O'Donovan, Ellen O'Malley, Ethel O'Shea, and many more. This leads, for the first time, to a full portrait of the Irish theatre that was produced in London during the 1920s in not only the West End, but also in smaller London theatres and in suburban repertory theatres"-- Provided by publisher.